Tatak Pilipino [episode no. 64] . ([Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
HIstorical rap calendar events of March (5 min.) -- Gloria Romero (10 min.) -- Carmen Rosales (10 min.) -- Encantasa (15 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Romero, Gloria; Rosales, Carmen; Fairies -- Philippines; Philippines -- History